Inscription on the Entrance Gate - Temples of India Project Team (Jio Institute, 2024)
Close-up of the inscription on the entrance gate, above the lintel. The inscription states that in 1464/1514 CE (VS 1521/71) the Bhandaprasada was built during the reign of Rao Lunkaran. The date is not clear. The inscription is copied here from the inscription in the antarala (antechamber) of the temple.